Effect of Crumb Rubber and Warm Mix Additives on Asphalt Aging, Rheological, and Failure Properties - Agrawal, Prashant (2014)
Thesis (Master, Chemistry) -- Queen's University, 2014-01-30 11:56:43.978 Asphalt-rubber mixtures have been shown to have useful properties with respect to distresses observed in asphalt concrete pavements. The most notable change in properties is a large increase in viscosity and improved low-temperature cracking resistance. Warm mix additives can lower production and compaction temperatures. Lower temperatures reduce harmful emissions and lower energy consumption, and thus provide environmental benefits and cut costs. In this study, the effects of crumb rubber modification on various asphalts such as California Valley, Boscan, Alaska North Slope, Laguna and Cold Lake were also studied. The materials used for warm mix modification were obtained from various commercial sources. The RAF binder was produced by Imperial Oil in their Nanticoke, Ontario, refinery on Lake Erie. A second commercial PG 52-34 (hereafter denoted as NER) was obtained/sampled during the construction of a northern Ontario MTO contract. Some regular tests such as Dynamic Shear Rheometer (DSR) and Bending Beam Rheometer (BBR), Multiple Stress Creep Recovery (MSCR) and some modified new protocols such as the extended BBR test (LS-308) and the Double-Edge Notched Tension (DENT) test (LS-299) are used to study, the effect of warm mix and a host of other additives on rheological, aging and failure properties. A comparison in the properties of RAF and NER asphalts has also been made as RAF is good quality asphalt and NER is bad quality asphalt. From the studies the effect of additives on chemical and physical hardening tendencies was found to be significant. The asphalt samples tested in this study showed a range of tendencies for chemical and physical hardening. M.Sc.